Novel CSF biomarkers to discriminate FTLD and its pathological subtypes - del Campo, Marta (Ann Clin Transl Neurol, 2018)
OBJECTIVE: Frontotemporal lobar degeneration (FTLD) is the second most prevalent dementia in young patients and is characterized by the presence of two main protein aggregates in the brain, tau (FTLD‐Tau) or TDP43 (FTLD‐TDP), which likely require distinct pharmacological therapy. However, specific diagnosis of FTLD and its subtypes remains challenging due to largely overlapping clinical phenotypes. Here, we aimed to assess the clinical performance of novel cerebrospinal fluid (CSF) biomarkers for discrimination of FTLD and its pathological subtypes. METHODS: YKL40, FABP4, MFG‐E8, and the activities of catalase and specific lysosomal enzymes were analyzed in patients with FTLD‐TDP (n = 30), FTLD‐Tau (n = 20), AD (n = 30), DLB (n = 29), and nondemented controls (n = 29) obtained from two different centers. Models were validated in an independent CSF cohort (n = 188). RESULTS: YKL40 and catalase activity were increased in FTLD‐TDP cases compared to controls. YKL40 levels were also higher in FTLD‐TDP compared to FTLD‐Tau. We identified biomarker models able to discriminate FTLD from nondemented controls (MFG‐E8, tTau, and Aβ (42); 78% sensitivity and 83% specificity) and non‐FTLD dementia (YKL40, pTau, p/tTau ratio, and age; 90% sensitivity, 78% specificity), which were validated in an independent cohort. In addition, we identified a biomarker model differentiating FTLD‐TDP from FTLD‐Tau (YKL40, MFGE‐8, βHexA together with βHexA/tHex and p/tTau ratios and age) with 80% sensitivity and 82% specificity. INTERPRETATION: This study identifies CSF protein signatures distinguishing FTLD and the two main pathological subtypes with optimal accuracy (specificity/sensitivity > 80%). Validation of these models may allow appropriate selection of cases for clinical trials targeting the accumulation of Tau or TDP43, thereby increasing their efficiency and facilitating the development of successful therapies.